Graphene–bimetallic nanoparticle composites with enhanced electro-catalytic detection of bisphenol A. (2nd November 2016) - Pogacean, Florina; Biris, Alexandru R; Socaci, Crina; Coros, Maria; Magerusan, Lidia; Rosu, Marcela-Corina; Lazar, Mihaela D; Borodi, Gheorghe; Pruneanu, Stela
Abstract: This study brings for the first time novel knowledge about the synthesis by catalytic chemical vapor deposition with induction heating of graphene–bimetallic nanoparticle composites (Gr–AuCu and Gr–AgCu) and their morphological and structural characterization by transmission electron microscopy, Raman spectroscopy, and x-ray powder diffraction. Gold electrodes modified with the obtained materials exhibit an enhanced electro-catalytic effect towards one of the most encountered estrogenic disruptive chemicals, bisphenol A (BPA). The BPA behavior in varying pH solutions was investigated using the electrochemical quartz crystal microbalance, which allowed the accurate determination of the number of molecules involved in the oxidation process. The modified electrodes promote the oxidation of BPA at significantly lower potentials (0.66 V) compared to bare gold (0.78 V). In addition, the peak current density recorded with such electrodes greatly exceeded that obtained with bare gold (e.g. one order of magnitude larger, for a Au/Gr–AgCu electrode). The two modified electrodes have low detection limits, of 1.31 × 10 −6 M and 1.91 × 10 −6 M for Au/Gr–AgCu and Au/Gr–AuCu, respectively. The bare gold electrode has a higher detection limit of 5.1 × 10 −6 M. The effect of interfering species (e.g. catechol and 3-nitrophenol) was also investigated. Their presence influenced not only the BPA peak potential, but also the peak current. With both modified electrodes, no peak currents were recorded below 3 × 10 −5 M BPA.